Interpretação e realização do eletrocardiograma: pré e pós conhecimento de estudantes de enfermagem - Gastaldi, Amanda Adabo (Universidade Federal de São Carlos, 2022)
This work aims to analyze the knowledge of nursing students about the interpretation and performance of the electrocardiogram before and after the online training. This is an exploratory, descriptive, cross-sectional study with a quantitative approach. Carried out in four stages: 1) Application of four pre-theoretical training questionnaires; 2) Construction of an educational material on electrocardiogram interpretation and heart rhythm recognition; 3) Online theoretical training; 4) Application of the post-training questionnaire to assess its effectiveness, aiming to assess changes in theoretical and cognitive knowledge about ECG interpretation and heart rhythm recognition in different contexts of health services. We sought to summarize and organize the data obtained through descriptive statistical analysis, carried out by the Microsoft Excel® Software. The sample consisted of 28 (100%) nursing students, on the theoretical guidance on ECG received during graduation, 10 (35.7%) of the students received adequate guidance and, after theoretical training, 23 (82.1% ) students considered the guidelines adequate; 7 (25%) of the students knew how to differentiate an ECG within the normality of the exam with alterations, which increased to 22 (78.6%) after training. Regarding the competence to differentiate an ECG within the normality of exam with alterations, 7 (25%) of the students knew how to differentiate, which increased to 22 (78.6%) after training. As for the interpretation of the ECG and recognition of heart rhythms, there was a significant increase in the percentage of correct answers, and the pre-training questionnaire ranged from 3 (10.7%) to 20 (71.4%), while in the post-training period it ranged from a minimum from 17 (60.7%) correct answers to 28 (100%). There was a clear improvement in the performance of students before and after theoretical training. It was concluded that the performance, analysis and interpretation of the ECG is essential for the training to be qualified and for these students to become qualified health professionals and avoid possible complications that can be identified in time to carry out an immediate intervention as long as there is knowledge and decision making. The importance of expanding training in this area is also highlighted so that nursing students can be qualified as professionals.
Interpretation and realization of electrocardiogram: pre and post knowledge of nursing students
Keywords: Ritmos cardíacos; Estudante de enfermagem; Eletrocardiograma; Heart rhythms; Nursing student; Electrocardiogram; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA